Checklist on the Quality of the Repetitive Peripheral Magnetic Stimulation (rPMS) Methods in Research: An International Delphi Study - Schneider, Cyril; Zangrandi, Andrea; Sollmann, Nico; Bonfert, Michaela Veronika; Beaulieu, Louis-David; , the rPMS Consensus Group (Frontiers in Neurology, 2022)
An increasing number of clinical research studies have used repetitive peripheral magnetic stimulation (rPMS) in recent years to alleviate pain or improve motor function. rPMS is noninvasive, painless, and administrated over peripheral nerve, spinal cord roots, or a muscle using a coil affixed to the skin and connected to a rapid-rate magnetic stimulator. Despite the clinical impact and scientific interest, the methodological inconsistencies or incomplete details and findings between studies could make the rPMS demonstration difficult to replicate. Given the lack of guidelines in rPMS literature, the present study aimed at developing a checklist to improve the quality of rPMS methods in research. An international panel of experts identified among those who had previously published on the topic were enrolled in a two-round web-based Delphi study with the aim of reaching a consensus on the items that should be reported or controlled in any rPMS study. The consensual rPMS checklist obtained comprises 8 subject-related items (e.g., age, sex), 16 methodological items (e.g., coil type, pulse duration), and 11 stimulation protocol items (e.g., paradigm of stimulation, number of pulses). This checklist will contribute to new interventional or exploratory rPMS research to guide researchers or clinicians on the methods to use to test and publish rPMS after-effects. Overall, the checklist will guide the peer-review process on the quality of rPMS methods reported in a publication. Given the dynamic nature of a consensus between international experts, it is expected that future research will affine the checklist.